An efficient model for simulation of temperature field of steel-concrete composite beam bridges. (September 2022) - Fan, Jian-Sheng; Li, Bao-Luo; Liu, Cheng; Liu, Yu-Fei
Abstract: Thermal performance between steel and concrete differs significantly and leads to the complexity of the temperature field and effect of steel–concrete composite bridges. Refined numerical models and accurately calibrated thermal parameters can solve the transient analysis of complex temperature fields. However, the method is inefficient and difficult to apply to analyzing massive historical data in calculating design temperature loads. In this paper, a vertical discrete and dimensionality-reduced model of the steel–concrete composite bridge is deduced and established for rapid temperature load calculation. A MATLAB-based state equation solving method is proposed to implement the one-dimensional efficient numerical model. Besides, an outdoor sunshine experiment is conducted to study the temperature field. The outdoor sunshine experiment measurements and refined model simulations verify the efficient numerical model. The computational efficiency of the efficient model is nearly 1000 times higher than that of the refined model, achieving rapid calculation of the composite bridge temperature field. The efficient thermal model proposed in this paper provides a powerful tool for analyzing the temperature field and effect and calculating the design temperature load of the composite bridge.